Multiple Epitopes in the Murine Cytomegalovirus Early Gene Product M84 Are Efficiently Presented in Infected Primary Macrophages and Contribute to Strong CD8(+)-T-Lymphocyte Responses and Protection following DNA Immunization - Ye, Ming (American Society for Microbiology, 2004)
We previously demonstrated that after vaccination of BALB/c mice with DNA encoding murine cytomegalovirus (MCMV) IE1 or M84, a similar level of protection against MCMV infection was achieved. However, the percentage of antigen-specific CD8(+) T cells elicited by IE1 was higher than that by M84 as measured by intracellular cytokine staining when splenocytes were stimulated with an epitope peptide (M. Ye at al., J. Virol. 76:2100-2112, 2002). We show here that after DNA vaccination with M84, a higher percentage of M84-specific CD8(+) T cells was detected when splenocytes were stimulated with J774 cells expressing full-length M84. When the defined M84 epitope 297-305 was deleted, the mutant DNA vaccine was still protective against MCMV replication and induced strong M84-specific CD8(+)-T-cell responses. The M84 gene was subsequently subcloned into three fragments encoding overlapping protein fragments. When mice were immunized with each of the M84 subfragment DNAs, at least two additional protective CD8(+)-T-cell epitopes were detected. In contrast to strong responses after DNA vaccination, M84-specific CD8(+)-T-cell responses were poorly induced during MCMV infection. The weak M84-specific response after MCMV infection was not due to poor antigen presentation in antigen-presenting cells, since both J774 macrophages and primary peritoneal macrophages infected with MCMV in vitro were able to efficiently and constitutively present M84-specific epitopes starting at the early phase of infection. These results indicate that antigen presentation by macrophages is not sufficient for M84-specific CD8(+)-T-cell responses during MCMV infection.